THE OPTIMIZATION OF PUBLIC TRAFFIC EDUCATION TO REDUCE THE RATE OF TRAFFIC ACCIDENTS IN THE POLICE STATION OF PEKALONGAN AREA - Alan Huda Zahira (Police Studies Review, 2022)
Today, the vehicle is an vital means of transportation for the mobility of people, therefore the number of vehicles is always increasing every time. The increasing number of vehicles causes of traffic accidents increasing. There are two factors that cause accidents, human factors and environtment factors. So, the public traffic education carried out by the security and safety unit of the Pekalongan police traffic unit has an important role in reducing the number of traffic accidents. The research location for this final project is in the jurisdictions of resort police in Pekalongan area. There are several problems discussed in this research, including how to implement the public traffic education carried out by the security and safety unit to reduce the number of traffic accidents and the efforts of the security and safety unit to optimize the public traffic education. The writer aims to explain the activities implementation of public traffic education and find the efforts to optimize public traffic education by the security and safety unit to reduce traffic accidents. The research approach in this final project is qualitative research using field research methods or research in the field. In order to discuss the problem, the author uses an analytical in the form of several theories and concepts, including management theory, and SWOT analysis theory. The results of the study indicate that the implementation of public traffic education and the efforts to optimize public traffic education by the security and safety unit to reduce the number of traffic accidents in the Pekalongan City Police are still not optimal. There are several factors, including the lack of human resources in the security and safety unit, the absence of a vocational education and the limited infrastructure by the security and safety unit. So, it is necessary to have a solution in optimizing the activities of the public traffic education in order to reduce the occurrence of traffic accidents.